A Collaborative Problem-Solving Psychoeducational Approach Implemented in Underresourced South African Schools. Issue 4 (2nd October 2019) - Amod, Zaytoon
ABSTRACT: Innovative service delivery approaches based on the trends and developments in education and psychology are required to address the scarcity of professional resources in developing countries such as South Africa. This article presents a description of a 21-month project in which five educational psychologists and 18 school-based teacher support teams provided psychoeducational support within their schools using a collaborative problem-solving approach. A mixed-methods research design using questionnaires and focus group interviews was adopted. School-based support team members and referring teachers perceived this approach as being a viable means of providing support to teachers, learners, and parents/caregivers. Teachers highlighted the successes and challenges they experienced as well as their need for continued professional training and school district support. The implications of these findings for practice are discussed, particularly with regard to service provision in underresourced community settings.